STEM Flexibel Model in Kindergarten - Lestari, Maya; Kurniati, Euis (PAEDAGOGIA, 2021)
The purpose of this study is to explore how the concept of STEM were used and negotiated by teachers in kindergarten. Science, Technology, Engineering, and Mathematics are inseparable parts of everyday life. This study was focused on teachers' perspectives on STEM learning in kindergarten level. STEM learning in this article included activities integrated into the existing themes in kindergarten. STEM learning involves children's creativity and stimulation to solve problems, know the solutions, and think logically, mathematically, and critically. In its implementation, STEM learning cannot be separated from the teachers' perspectives. Thus, analysing teachers' perspectives on STEM learning in kindergarten, including what activities were included, will contribute to early childhood education development. This research was a qualitative study and carried out using an online interview. Drawing on data from 50 kindergarten teachers in Indonesia as the respondents, findings of this study indicated that the term STEM was still considered unfamiliar for kindergarten teachers, the implementation and benefits of STEM in kindergarten also implemented with a more flexible model.